2017
DOI: 10.3889/oamjms.2017.149
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Oxidant and Antioxidant Markers to Asthma Severity in Egyptian Asthmatic Children

Abstract: BACKGROUND:Asthma is a chronic airway disease which is characterized by oxidant antioxidant imbalance with the generation of oxidative stress related mediators.AIM:The study aimed to evaluate the role of asymmetric dimethylarginine, and malondialdehyde as oxidant markers and serum paraoxonase activity as an antioxidant marker in asthma, and to determine their relationship to the asthma severity and lung function among asthmatic children in Egypt.PATIENTS AND METHODS:This case control study was conducted on six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…This study revealed that there is statistically significant increase of serum ADMA (P = 0.006), which was reported previously by Carraro et al (2013), who evaluated the levels of ADMA in both serum and exhaled breath condensation, and proved its role in different pathological processes of bronchial asthma such as (airway irritation, oxidative stress, bronchial hyperresponsiveness, and collagen deposition). El-Alameey et al in (2017) found that serum concentrations of oxidizing agent markers such as ADMA and malondialdehyde were increased in patients complaining of asthma, while an antioxidant marker such as paraoxonase was mainly reduced in comparison with controls. Moreover, Ito et al (2018) found that irrespective to weight, the concentrations of ADMA are more prominent in both asthmatic grown-ups and children in comparison with their respective controls, and plasma L-arginine levels are lower in healthy obese subjects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study revealed that there is statistically significant increase of serum ADMA (P = 0.006), which was reported previously by Carraro et al (2013), who evaluated the levels of ADMA in both serum and exhaled breath condensation, and proved its role in different pathological processes of bronchial asthma such as (airway irritation, oxidative stress, bronchial hyperresponsiveness, and collagen deposition). El-Alameey et al in (2017) found that serum concentrations of oxidizing agent markers such as ADMA and malondialdehyde were increased in patients complaining of asthma, while an antioxidant marker such as paraoxonase was mainly reduced in comparison with controls. Moreover, Ito et al (2018) found that irrespective to weight, the concentrations of ADMA are more prominent in both asthmatic grown-ups and children in comparison with their respective controls, and plasma L-arginine levels are lower in healthy obese subjects.…”
Section: Discussionmentioning
confidence: 94%
“…The lung is a predominant supply of asymmetric dimethylarginine (ADMA) (El-Alameey et al, 2017). Little information could be recognized about the role of (ADMA) in the diseases of airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides inflammation in the airways, bronchoconstriction may also be triggered by various types of proteolytic and oxidative damage. Therefore, it is argued that anti-inflammatory and anti-oxidant agents will prevent the triggering of bronchoconstriction which constitutes the fundamental mechanism in asthma (4,6,9,12). It has been reported that zinc, which has anti-oxidant, anti-apoptotic, anti-inflammatory and anti-allergic properties, is important in dermatologic and respiratory diseases, while zinc deficiency plays an important role in the pathogenesis and severity of dermatologic and respiratory diseases (2,8,11).…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines are released from activated inflammatory cells and stimulate polymorphic leukocytes to produce reactive oxygen species (ROS). Antioxidants increase in an attempt to balance the increased oxidative stress (3). The paraoxonase1 (PON-1) enzyme is an endogenous antioxidant that plays a critical role in the defensive system against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%